Physical chemistry - Atkins, Peter W. (U.S.A Oxford University Press, 1986)
This manual contains the authors' detailed solutions to almost every one of the problems contained in the third edition of Physical Chemistry . It will be valuable both to the instructors and lecturers who have adopted the parent text, and to the students themselves.
Keywords: physical chemistry,solution manual